ADOPTION OF SOFTWARE AS A SERVICE (SAAS) IN SMALL AND MEDIUM-SIZED HOTELS IN TIRANA - Alba Demneri Kruja; Xhimi Hysa; Teoman Duman; Ava Tafaj (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2019)
Technology moves with a rapid pace and it has touched every aspect of the hospitality industry. Nowadays, this huge industry is facing significant technological changes especially in the hotel sector. With the continuing growth of modern technologies in hotel management (e.g. SaaS, PMS, CRM, smart devices, Internet of things), and other aspects of industry 4.0, readiness of sector representatives to adopt such new technological advancements appears as a worthy research topic. This research aimed to identify the adoption of SaaS (Software as a Service) technology in small and medium-sized hotels in Tirana, Albania and measure hotel owners/managers’ willingness to implement this technology in their properties. As part of the data collection process, a structured interview was conducted with 75 hotel owners and managers. Results show that SaaS technology implementation is very limited in the sampled hotels. Majority of the sampled hotels extensively rely on traditional property management systems. Nevertheless, other findings of the study show that hotel managements demonstrate high willingness to implement SaaS system in their hotel management. This willingness was found to be more prevalent among newly hired, more educated, younger managers as compared to older age hotel owners. A number of implications are discussed for local authorities, SaaS marketers and hotel managements to implement SaaS system in small and medium-sized hotels in Tirana.